Some Economic Consequences of Global Aging : A Discussion Note for the World Bank - Lee, Ronald (World Bank, Washington, DC, 2013)
The note describes the importance of population aging world-wide, clarifying its prevalence among middle- and low-income countries, which suggests that many developing countries are getting old before they are growing rich. The note then asks in what way population aging is an economic problem and what are the specific challenges facing developing countries in this process. The note argues against the common, time-bomb perception?, and clarifies how a simplistic extrapolation from the impact of aging on single programs such as public pensions gives a misleading impression about the more general macroeconomic consequences of population aging, where numerous elements contribute to a more nuanced result. The note briefly discusses various topics of importance in the population aging debate, including: intergenerational flows, social contracts, the risk management element of old-age policies, and the impact of aging on health care costs. The note seeks to share a number of counterintuitive or simply non-intuitive facts, including: (i) the large impact of declines in fertility on population aging (often more important than increases in longevity); (ii) the impact of increased life expectancy on working age populations (often larger than among old age populations); (iii) the positive impact of aging on capital intensity; (iv) the need to include education in assessments of intergenerational equity (these often simply look at who pays for old-age pensions and health services); and (v) the role of long-term care programs as insurance for risks faced by young adults.